Regendering the Nation: The Khwajasara Movement in Pakistan - Hamzić, Vanja (2013)
This paper presents a critical ethnographic account of Pakistani khwajasara, based on the author’s most recent fieldwork in Lahore in 2011. Khwajasara, known elsewhere in the Indian Subcontinent as hijra, are Pakistani gender-variant subject position, whose cultural memory and historical roots run deep into the region’s Mughal past (and beyond). This piece attempts to recount their long-lasting social and political battle with Pakistani judicial and political system, against a backdrop of an important episode in their struggle – the 23 December 2009 judgment of the Supreme Court of Pakistan’s Chief Justice granting them a ‘third gender’ status on their state identification documents – which is yet to be implemented. One of the paradigmatic facets of khwajasara, analysed here primarily as a political movement rather than an essentialised identitary script, is their decidedly subversive approach to nationalism. In it, the dominant concepts of ‘Pakistanness’ are exposed to a peculiar form of ‘gender critique’, one in which gender difference serves as a litmus paper for the nation’s grand social and political designs. This approach is operationalised through a number of strategic public actions, including protest marches, domestic litigation and collaboration with workers’ unions, as well as through the everyday life of khwajasara. It construes khwajasara as a Pakistani subjectivity par excellence, which at the same time represents a dire alterity to the postcolonial nationalistic forms of the Pakistani selfhood, deployed along the religious, ethnic and class-based fault lines. As such, khwajasara embrace and even salvage ‘Pakistanness’, albeit only to showcase the abundant perils of its daily hegemonic use. In order to regender the imagined collectives that Pakistani society is composed of, khwajasara seek to engage them subversively as ‘fellow citizens’ – compatriots in a larger ‘nation-wide’ struggle. There is a premeditated element of irony involved in such acts, for khwajasara are typically relegated to the ...